Binky under pressure - Spires, Ashley, 1978- (Spires, Ashley, 1978- Binky adventure., 2011)
Binky, a house cat that believes he is a space cat, is dismayed when Gracie, a too-perfect foster cat, comes to live at his space station, and decides to investigate to learn the truth about this unwelcome guest.